CLINICAL AND STATISTICAL ANALYSIS OF COMBINED INJURIES OF THE NOSE AND PARANASAL SINUSES - Bakiyeva SH.X.,; Karimberdiyev B.I,; Djurayev J.A., (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This study presents a clinical and statistical analysis of 140 patients with combined injuries of the nose and paranasal sinuses treated at a multidisciplinary clinic.  The  study  evaluates  demographic  characteristics,  causes  of  injury,  types  of trauma, diagnostic methods, and treatment outcomes. The results indicate that such injuries are more common among males of working age. Domestic trauma and road traffic  accidents  were  identified  as  the  leading  causes.  The  findings  highlight  the importance  of  timely  diagnosis  and  appropriate  surgical  management  in  reducing complications.